Carbazole phosphate material as well as preparation method and application thereof
By using carbazole phosphate materials and technical means of introducing pyridine groups, small molecule hole transport materials have large structural rigidity and poor film formation performance in perovskite solar cells, and the application of efficient and stable large-area perovskite solar cells has been solved.
Patent Information
- Application Number
- CN202411667728.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Existing small molecule hole transport materials have problems such as large structural rigidity, poor film formation performance, poor structural stability and high doping cost in perovskite solar cells, which limits the large-scale commercial application of perovskite solar cells.
Carbazole phosphate materials are used as hole transport layer, and their photophysical, electrochemical and photovoltaic properties are adjusted by introducing pyridine groups, improving the film-forming performance and structural stability of perovskite films, and reducing doping costs.
The hole transport materials with uniform coating on rough surfaces, high hole extraction selectivity and low interface electron trap density are realized, the photoelectric conversion efficiency of perovskite solar cells is improved, and the application of low-cost, high-performance, stable and large-area perovskite solar cells is realized.
Smart Images

Figure CN119504858A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaic technology, and in particular to a carbazole phosphate material, a preparation method and application thereof. Background Art
[0002] Perovskite solar cells (PSCs) are devices that use perovskite-type organic metal halide semiconductors as light-absorbing materials to directly convert light energy into electrical energy through the photovoltaic effect. Among them, trans-structured PSCs show great potential in commercial applications. The hole transport layer is an important component of perovskite solar cells, and the continuous development of new hole transport materials (HTMs) is a key factor in the preparation of efficient and stable perovskite solar cells. Polymer hole transport materials have great potential in the preparation of large-area trans-perovskite solar cells due to their excellent film-forming properties and solvent resistance, and their adaptability to low-cost printing technology.
[0003] In inverse perovskite solar cells, hole transport materials, as important transport layer materials between the perovskite layer and the transparent electrode, are not only responsible for the extraction and transport of holes and blocking the flow of electrons, but also directly affect the crystallization and film-forming properties of perovskite, playing a decisive role in improving battery performance and realizing large-scale commercial applications.
[0004] At present, HTMs in perovskite solar cells are mainly divided into three categories: inorganic hole transport materials, organic small molecule hole transport materials and organic polymer hole transport materials. Small molecule HTMs have a clear structure and molecular weight. According to the spatial structure, they can be roughly divided into three categories: linear structure, spirocyclic structure and star structure. They can also be divided into dithienylpyrrole type, triphenylamine type, carbazole type, bifluorene type, thiophene type, etc. according to the different groups contained in the molecular structure. Small molecule HTMs have become the most common type of HTMs in perovskite solar cells due to their advantages such as synthetic varieties, adjustable properties, high purity and easy solution processing. However, due to the defects in the inherent characteristics of small molecule HTMs, it has brought obstacles to the large-scale commercialization of PSCs. Summary of the invention
[0005] The main purpose of the present invention is to provide a phosphate carbazole material, a preparation method and application thereof, so as to solve the problems of high structural rigidity, poor film-forming performance, poor structural stability and high doping cost of small molecule hole transport materials in the prior art.
[0006] In order to achieve the above object, according to one aspect of the present invention, a phosphate carbazole material is provided, having a structure shown in general formula (I):
[0007] Wherein, A is O or S.
[0008] According to another aspect of the present invention, a method for preparing the above-mentioned phosphate carbazole material of the present invention is provided. The preparation method is carried out under the protection of an inert gas and comprises the following steps: Step S1: A first palladium catalyst and a first base are mixed and dissolved in a first solvent, and a first coupling reaction is performed to obtain Where A is O or S; Step S2, Dibromobutane, a substitution catalyst, and a second base are mixed to carry out a first nucleophilic substitution reaction to obtain Step S3: Triethyl phosphite was mixed and a second nucleophilic substitution reaction was performed to obtain Step S4: The second palladium catalyst and the third base are mixed and dissolved in the second solvent, and a second coupling reaction is performed to obtain Step S5: The trimethylsilyl bromide and 1,4-dioxane are mixed and subjected to a hydrolysis pre-reaction to obtain a solid product; the solid product is dissolved in methanol and water is added dropwise to perform a hydrolysis reaction to obtain
[0009]
[0010] Further, in step S1, the first palladium catalyst comprises tris(dibenzylideneacetone)dipalladium and 1,1'-bis(diphenylphosphine)ferrocene ligand, and the molar ratio of the two is 1:(0.8-1.2); and / or and The molar ratio is 1:(1.0-1.1); and / or The molar ratio of the first palladium catalyst to the first palladium catalyst is 1:(0.08-0.12); and / or the reaction temperature of the first coupling reaction is 100-140° C., and the reaction time is 10-14 hours.
[0011] Further, in step S2, the replacement catalyst comprises tetrabutylammonium bromide; and / or The ratio of the amount of substance to the volume of dibromobutane is (2.5-3.0 mmol): 20 mL; and / or The molar ratio of the substitution catalyst is 1:(0.08-0.12); and / or the reaction temperature of the first nucleophilic substitution reaction is 60-70° C., and the reaction time is 10-14 hours.
[0012] Further, in step S3, The ratio of the amount of substance to the volume of triethyl phosphite is (2.8-3.2 mmol):10 mL; and / or the reaction temperature of the second nucleophilic substitution reaction is 130-160° C., and the reaction time is 10-14 h.
[0013] Further, in step S4, the second palladium catalyst comprises palladium acetate and tri-tert-butylphosphine ligand, and the molar ratio of the two is 1:(0.8-1.2); and / or and The molar ratio is 1:(2.0-2.4); and / or The molar ratio of the catalyst to the second palladium catalyst is 1:(0.08-0.12); and / or the reaction temperature of the second coupling reaction is 65-85° C., and the reaction time is 6-15 hours.
[0014] Further, in step S5, The molar ratio of trimethylsilyl bromide to trimethylsilyl bromide is 1:(9.5-10.5); and / or The ratio of the amount of substance to the volume of 1,4-dioxane is (1.8-2.2 mmol):10 mL; and / or the temperature of the hydrolysis pre-reaction is 20-30° C., and the time is 10-14 h; the temperature of the hydrolysis reaction is 20-30° C., and the time is 10-14 h.
[0015] Further, the inert gas includes nitrogen and / or argon; and / or the first base, the second base and the third base independently include one or more of sodium tert-butoxide, potassium hydroxide, potassium carbonate and sodium carbonate; and / or the first solvent includes toluene and / or tetrahydrofuran; and / or the second solvent includes toluene and isopropanol, and the weight ratio between the two is 1:(6-10).
[0016] According to another aspect of the present invention, a hole transport layer is provided, comprising the above-mentioned phosphate carbazole material of the present invention, or comprising the phosphate carbazole material obtained by the above-mentioned preparation method of the present invention.
[0017] According to another aspect of the present invention, a perovskite solar cell is provided, comprising the hole transport layer of the present invention.
[0018] The technical solution of the present invention is applied, and carbazole phosphate is used as the main structure, which has the ability to be evenly coated on rough surfaces and high hole extraction selectivity, as well as low interface electron trap density, so it can be used as an excellent hole selective contact layer. At the same time, pyridine groups are introduced therein to adjust the photophysical, electrochemical and photovoltaic properties, showing improved surface wettability of the perovskite precursor solution, thereby inducing the growth of high-quality perovskite films; the N atoms and amino groups with lone pairs of electrons in pyridine can both react with uncoordinated Pb in the perovskite. 2+ The formation of coordinated bond ions effectively reduces the defect density in the perovskite film; the introduction of pyridine groups can also enhance hole mobility and improve energy levels, thereby improving interface charge extraction and reducing interface V ocloss; pyridine generates excellent inherent thermal / photostability and stronger interaction at the interface to release interface stress, so that the thermal performance and operational stability of perovskite solar cells are improved. The phosphate carbazole hole transport material of the present invention has good solubility, film-forming property, high hole mobility and energy level matching with perovskite. It can be used as an undoped hole transport material in perovskite solar cells to obtain good photoelectric conversion efficiency, and realize low-cost, high-performance, stable, large-area perovskite solar cell applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0020] Figure 1 shows the nuclear magnetic resonance spectrum of the phosphate carbazole material according to Example 1 of the present invention;
[0021] Figure 2 shows the nuclear magnetic resonance spectrum of the phosphate carbazole material according to Example 2 of the present invention;
[0022] Figure 3 A schematic diagram of the structure of a perovskite solar cell according to an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0024] Unless otherwise specified, the "solution" in the present invention refers to an aqueous solution, "room temperature" refers to 20-30° C., and "overnight" refers to 12 hours.
[0025] As described in the background of the present invention, the existing technology has the problems of large structural rigidity, poor film-forming performance, poor structural stability and high doping cost of small molecule hole transport materials. In order to solve the above problems, in a typical embodiment of the present invention, a phosphate carbazole material is provided, having a structure shown in general formula (I):
[0026] Wherein, A is O or S.
[0027] During the research process, the inventors unexpectedly discovered that due to the rigid structure of small molecule HTMs and their low tolerance to perovskite precursor solutions, the films produced by small molecule HTMs always have pinhole morphology defects, are morphologically unstable under external stimuli, and many small molecule HTMs require the addition of dopants. These factors also pose obstacles to the large-scale commercialization of PSCs.
[0028] Currently, some of the most promising inverted perovskite solar cells are made of self-assembled monolayers (SAMs) containing carbazole phosphates (PAs), such as [2-(9H-carbazole-9-yl)ethyl]phosphate (2PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphate (MeO-2PACz), and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphate (Me-4PACz). They can be used as excellent hole-selective contact layers, but their structure and performance still need to be improved.
[0029] The present invention uses phosphocarbazole as the main structure, which has the ability to be evenly coated on rough surfaces and has high hole extraction selectivity, as well as low interface electron trap density, so it can be used as an excellent hole-selective contact layer. At the same time, pyridine groups are introduced into it to adjust the photophysical, electrochemical and photovoltaic properties, showing improved surface wettability of the perovskite precursor solution, thereby inducing the growth of high-quality perovskite films; the N atoms and amino groups with lone pairs of electrons in pyridine can both bind to the uncoordinated Pb in the perovskite. 2+ The formation of coordinated bond ions effectively reduces the defect density in the perovskite film; the introduction of pyridine groups can also enhance hole mobility and improve energy levels, thereby improving interface charge extraction and reducing interface V oc loss; excellent intrinsic thermal / photostability and stronger interactions at the interface by pyridine to release interfacial stress, resulting in improved thermal performance and operational stability of perovskite solar cells.
[0030] The phosphate carbazole hole transport material of the present invention has good solubility, film-forming property, high hole mobility and energy level matching that of perovskite. It can be used as an undoped hole transport material in perovskite solar cells to obtain good photoelectric conversion efficiency, and realize low-cost, high-performance, stable and large-area perovskite solar cell applications.
[0031] In another typical embodiment of the present invention, a method for preparing the above-mentioned phosphate carbazole material of the present invention is also provided. The preparation method is carried out under the protection of an inert gas and comprises the following steps: Step S1: A first palladium catalyst and a first base are mixed and dissolved in a first solvent, and a first coupling reaction is performed to obtain Where A is O or S; Step S2, Dibromobutane, a substitution catalyst, and a second base are mixed to carry out a first nucleophilic substitution reaction to obtain Step S3: Triethyl phosphite was mixed and a second nucleophilic substitution reaction was performed to obtain Step S4: The second palladium catalyst and the third base are mixed and dissolved in the second solvent, and a second coupling reaction is performed to obtain Step S5: The trimethylsilyl bromide and 1,4-dioxane are mixed and subjected to a hydrolysis pre-reaction to obtain a solid product; the solid product is dissolved in methanol and water is added dropwise to perform a hydrolysis reaction to obtain
[0032]
[0033] Specifically, the present invention first The first palladium catalyst and the first base are mixed and dissolved in the first solvent. Under alkaline conditions and palladium catalysis, the amine and the aryl halide undergo CN coupling, i.e., Buchwald-Hartwing coupling reaction, to obtain
[0034] Secondly, Dibromobutane, a substitution catalyst, and a second base are mixed under alkaline conditions. Nucleophilic substitution with dibromobutane gives
[0035] Afterwards, The reaction is carried out in two steps of SN2 reaction. The first step is that triethyl phosphite reacts with The phosphonium salt is formed by SN2 reaction; the second step is that the bromide ion of the phosphonium salt undergoes SN2 nucleophilic substitution on an ester alkyl group, and the reaction process is accompanied by the breaking of the CO bond and the formation of P=O, and finally the
[0036] Then, The second palladium catalyst and the third base are mixed and dissolved in the second solvent. Under alkaline conditions and palladium catalysis, the imine and the aryl halide undergo a Buchwald-Hartwing coupling reaction to obtain
[0037] Finally, Trimethylsilyl bromide and 1,4-dioxane are mixed and pre-hydrolyzed to obtain a solid product; the solid product is dissolved in methanol and water is added dropwise to perform a hydrolysis reaction. The mechanism of the phosphate hydrolysis reaction can be divided into two steps: the first step is the breaking of the phosphate bond, and the second step is the addition of water molecules. In the first step, the oxygen atom of the phosphate molecule accepts a proton to generate an intermediate, which is highly stable. In the second step, a water molecule enters the reaction system and reacts with the intermediate to obtain
[0038] The present invention introduces pyridine groups into HTMs through reasonable molecular engineering to adjust photophysical, electrochemical and photovoltaic properties; the prepared small molecule hole transport material has a novel molecular structure, low synthesis cost, good solubility, film-forming property, high hole mobility and energy level matching that of perovskite, and is used as an undoped hole transport material in an inverse perovskite solar cell to obtain a good photoelectric conversion efficiency, the preparation process is simple, and it is suitable for industrial production. In addition, the prepared phosphate carbazole hole transport material can be used in perovskite solar cells without being doped with any additives, and has repeatability and good application prospects.
[0039] The above-mentioned preparation method is carried out under the protection of inert gas throughout the process, effectively avoiding the influence of oxygen and moisture in the air on the reaction, ensuring the purity of the product and the smooth progress of the reaction, ensuring that each step is fully reacted, improving the reaction efficiency and product yield, and the preparation process is reasonably designed, with clear steps and good repeatability, which is conducive to industrial large-scale production and reduces manufacturing costs. In summary, the preparation method of the present invention not only ensures the high-quality synthesis of phosphate carbazole materials, but also simplifies the operation process, laying a solid foundation for the commercial application of high-performance perovskite solar cells.
[0040] In a preferred embodiment, in step S1, the first palladium catalyst comprises tris(dibenzylideneacetone)dipalladium and 1,1'-bis(diphenylphosphine)ferrocene ligand, and the molar ratio of the two is 1:(0.8-1.2); and / or and The molar ratio is 1:(1.0-1.1); and / or The molar ratio of the first palladium catalyst to the first palladium catalyst is 1:(0.08-0.12); and / or the reaction temperature of the first coupling reaction is 100-140° C., and the reaction time is 10-14 hours.
[0041] The use of the above palladium catalyst and the reasonable control of its composition molar ratio can further promote the CN coupling reaction, improve the reaction activity, and thus increase the product yield. The molar ratio of the reactant to the catalyst within the above range can make full use of the active sites of the catalyst, reduce the waste of catalytic activity, further improve the reaction rate and product purity, and the efficient use of the catalyst also reduces the preparation cost. The temperature and time of the first coupling reaction are controlled within the above range to promote the full reaction of the reactants, reduce side reactions, improve product selectivity, and are more conducive to obtaining a phosphoric acid carbazole material with moderate structural rigidity and excellent film-forming performance.
[0042] To further promote effective contact and dissolution between reactants and improve reaction efficiency, in a preferred embodiment, in step S2, the replacement catalyst includes tetrabutylammonium bromide; and / or The ratio of the amount of substance to the volume of dibromobutane is (2.5-3.0 mmol): 20 mL; and / or The molar ratio of the catalyst to the substitution catalyst is 1:(0.08-0.12); and / or the reaction temperature of the first nucleophilic substitution reaction is 60-70°C, and the reaction time is 10-14h. Selecting tetrabutylammonium bromide as the substitution catalyst and controlling its addition amount can not only effectively catalyze the nucleophilic substitution reaction and increase the reaction rate, but also reduce the side reactions of the excess catalyst, improve the selectivity of the reaction and the purity and yield of the product. The above temperature and time range can effectively promote the reactants to undergo nucleophilic substitution reactions, promote the full progress of the reaction, thereby increasing the yield of the product, and the obtained phosphate carbazole material has less structural rigidity, good film-forming properties and structural stability, reduces the doping cost, and improves the practicality and economic benefits of the material.
[0043] In a preferred embodiment, in step S3, The ratio of the amount of substance to the volume of triethyl phosphite is (2.8-3.2 mmol): 10 mL; and / or the reaction temperature of the second nucleophilic substitution reaction is 130-160°C, and the reaction time is 10-14 h. By setting the ratio within the above range, the contact between the reactants and the catalyst can be promoted, the efficient SN2 reaction can be promoted, and the reaction selectivity and product yield can be improved. Higher temperatures are more conducive to the formation of phosphonium salts and subsequent nucleophilic substitution of ester groups, which accelerates the reaction kinetics and significantly increases the reaction rate. At the same time, a longer reaction time can promote the full progress of the reaction and further improve the purity and yield of the product. The above conditions also promote the flexibility of the molecular structure, reduce the structural rigidity of the final material, improve the film-forming performance and structural stability, reduce the doping cost that may be required in subsequent applications, and reduce the difficulty of material processing.
[0044] For the purpose of more conducive to obtaining a phosphate carbazole material with low structural rigidity, good film-forming performance and high structural stability, in a preferred embodiment, in step S4, the second palladium catalyst comprises palladium acetate and tri-tert-butylphosphine ligand, and the molar ratio of the two is 1: (0.8-1.2); and / or and The molar ratio is 1:(2.0-2.4); and / or The molar ratio of the catalyst to the second palladium catalyst is 1:(0.08-0.12); and / or the reaction temperature of the second coupling reaction is 65-85° C., and the reaction time is 6-15 hours.
[0045] By selecting palladium acetate and tri-tert-butylphosphine ligand as the second palladium catalyst, and the molar ratio is controlled within a specific range, the activity and selectivity of the CN coupling reaction can be further improved, the reaction process can be accelerated, and the side reactions that may be caused by the excessive ligand can be reduced, thereby significantly increasing the yield of the product. The molar ratio of the reactant ratio is set to the above range to facilitate the full conduct of the reaction, so as to further improve the yield and purity of the reaction. Accurately controlling the amount of catalyst can reduce unnecessary catalyst waste to further reduce costs while improving the reaction selectivity and improving the product yield. The reaction temperature and reaction time of the second coupling reaction can promote the full conduct of the reaction in the above range.
[0046] In a preferred embodiment, in step S5, The molar ratio of trimethylsilyl bromide to trimethylsilyl bromide is 1:(9.5-10.5); and / or The ratio of the amount of substance to the volume of 1,4-dioxane is (1.8-2.2 mmol):10 mL; and / or the temperature of the hydrolysis pre-reaction is 20-30° C., and the time is 10-14 h; the temperature of the hydrolysis reaction is 20-30° C., and the time is 10-14 h.
[0047] Setting the molar ratio of the reactants to the above range can promote the effective conversion between the reactants, facilitate the uniform reaction, reduce the side reactions caused by the excess reactants, and thus significantly improve the yield of the product. When the temperature and time of the hydrolysis pre-reaction and the hydrolysis reaction are controlled within the above range, the reaction is mild and sufficient, reducing the decomposition or structural changes of the product that may be caused by high temperature, while ensuring the complete progress of the hydrolysis reaction, reducing the residue of unreacted substances, and having a positive effect on the structural rigidity and film-forming properties of the product. Mild hydrolysis reaction conditions also avoid the introduction of additional high-temperature treatment costs, which is conducive to controlling the economy of the entire preparation process. The final phosphate carbazole material has good structural stability and excellent film-forming properties. Because the reaction conditions are mild, no additional dopants are required, which effectively reduces the preparation cost of the material.
[0048] In order to further effectively isolate oxygen and water vapor, prevent oxidation and hydrolysis of reactants, ensure the smooth progress of the reaction, and improve the purity and yield of the product, in a preferred embodiment, the inert gas includes nitrogen and / or argon; and / or the first base, the second base and the third base independently include one or more of sodium tert-butoxide, potassium hydroxide, potassium carbonate and sodium carbonate; and / or the first solvent includes toluene and / or tetrahydrofuran; and / or the second solvent includes toluene and isopropanol, and the weight ratio of the two is 1: (6-10). The above alkaline reagents can not only accelerate the reaction process and increase the reaction rate, but also the use of these reagents helps to control the pH value of the reaction, improve the reaction selectivity, and reduce the generation of by-products, thereby further increasing the yield of the target product phosphate carbazole material. The above-mentioned solvent not only has good solubility, thereby improving the solubility of the reactants and promoting the full progress of the reaction, but also due to the difference in boiling point and polarity, it helps to control the temperature of the reaction system and the distribution of the reactants, ensuring the uniformity of the reaction and the quality of the reaction products, reducing the structural rigidity of the material, improving the film-forming performance and structural stability, reducing the subsequent doping costs that may be required, and significantly improving the synthesis efficiency of phosphate carbazole materials, ensuring the high purity and high yield of the product, while improving the performance of the material, making it more suitable for the preparation of commercial high-performance perovskite solar cells.
[0049] In order to further improve the purity of the products of each step, so as to further improve the structural stability, film-forming performance and photoelectric performance of the phosphate carbazole material, in a preferred embodiment, step S1 also includes a step of first purifying the reaction liquid, including: extracting the organic phase with a saturated sodium chloride aqueous solution and dichloromethane in a volume ratio of (10 to 15): 1, then drying with anhydrous magnesium sulfate, and then filtering, distilling under reduced pressure, and purifying with silica gel chromatography in sequence; and / or step S2 also includes a step of second purifying the reaction liquid, including: extracting the organic phase with a saturated sodium chloride aqueous solution and dichloromethane in a volume ratio of (10 to 15): 1, then drying with anhydrous magnesium sulfate, and then filtering, distilling under reduced pressure, and purifying with silica gel chromatography in sequence; and / or step S3 also includes a step of third purifying the reaction liquid, including: using a volume ratio of (10 to 15): 1 The organic phase is extracted with a saturated sodium chloride aqueous solution and dichloromethane in a volume ratio of (10-15):1, then dried with anhydrous magnesium sulfate, then filtered, distilled under reduced pressure, and finally recrystallized with an alcohol and dichloromethane in a volume ratio of (15-30):1; the alcohol is methanol or ethanol; and / or step S4 also includes a step of subjecting the reaction liquid to a fourth purification, including: extracting the organic phase with a saturated sodium chloride aqueous solution and dichloromethane in a volume ratio of (10-15):1, then drying with anhydrous magnesium sulfate, then filtering, distilled under reduced pressure, and finally recrystallized with an alcohol and dichloromethane in a volume ratio of (15-30):1; the alcohol is methanol or ethanol; and / or step S5 also includes a step of subjecting the reaction liquid to a fifth purification, including: recrystallizing with an alcohol and dichloromethane in a volume ratio of (15-30):1; the alcohol is methanol or ethanol.
[0050] In another typical embodiment of the present invention, a hole transport layer is also provided, including the above-mentioned phosphate carbazole material of the present invention, or including the phosphate carbazole material obtained using the above-mentioned preparation method of the present invention, which has a deeper HOMO energy level that matches the perovskite, has good mobility, is conducive to the extraction and transmission of holes, and has significantly improved transmission capacity.
[0051] In another typical embodiment of the present invention, a perovskite solar cell is also provided, comprising the hole transport layer of the present invention, which has significantly improved photoelectric performance. Specifically, the inverse quasi-two-dimensional perovskite solar cell device structure can be ITO glass / hole transport layer / quasi-two-dimensional perovskite / electron transport layer (PC61BM) / chromium (Cr) / gold (Au), wherein the hole transport layer is made of a phosphate carbazole hole transport material provided by the present invention. The preparation method of a trans-quasi-two-dimensional perovskite solar cell based on a phosphate carbazole hole transport material may include the following steps:
[0052] (1) Cleaning: The ITO glass sheet was ultrasonically cleaned with deionized water, acetone, and ethanol for 15 to 20 minutes in sequence, and then the residual solvent on the surface of the ITO was blown dry with a N2 air gun. The ITO glass sheet was then treated with oxygen plasma for 10 to 15 minutes, and then the ITO glass sheet was transferred to a nitrogen glove box.
[0053] (2) Preparation of hole transport layer: 3-15 mg of phosphate carbazole hole transport material was weighed and completely dissolved in 1 mL of chlorobenzene solution, and an appropriate amount of the solution was evenly added dropwise onto the ITO glass substrate, and spin-coated at 4000-5000 rpm for 20-30 seconds, and then annealed at 90-110° C. for 10 minutes;
[0054] (3) Preparation of perovskite layer: The ITO / hole transport layer substrate obtained above was cooled to room temperature, preheated at 130-140°C for 3-5 minutes, 50 μL of perovskite solution was spread over the ITO / hole transport layer substrate, spin coated at 3000-5000 rpm for 20-30 seconds, and then annealed at 90-100°C for 10 minutes to prepare a perovskite layer. The perovskite solution is prepared by mixing 3-bromo-benzylammonium iodide or 3-chlorobenzylammonium iodide with methylammonium chloride and lead iodide in DMF and DMSO in a certain molar ratio;
[0055] (4) Preparation of electron transport layer: The ITO / hole transport layer / perovskite substrate obtained above was cooled to room temperature, PC61BM was prepared into a 15 mg / mL solution, and then 40 μL of the PC61BM solution was spread over the ITO / hole transport layer / perovskite substrate, and spin-coated at 1000 rpm for 30 to 50 seconds;
[0056] (5) Preparation of electrodes: The above substrate is placed in a vacuum evaporation chamber, and Cr (6 nm) and Au (80 nm) are evaporated on the PC61BM layer respectively, thereby obtaining the desired inverse quasi-two-dimensional perovskite solar cell.
[0057] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0058] Example 1
[0059] The synthesis of PACZ-OMe, the synthesis route is as follows:
[0060]
[0061] Step S1, synthesis of the compound of formula (3): weigh the compound of formula (1) (1.1 g, 4 mmol), p-methoxyaniline (0.53 g, 4.2 mmol), Pd2(dba)3 (0.18 g, 0.2 mmol), DPPF (0.11 g, 0.2 mmol), sodium tert-butoxide (0.38 g, 4 mmol) and toluene into a flask, react at 120° C. for 12 hours. DCM extraction, drying over anhydrous magnesium sulfate, column chromatography with PE:DCM ratio of 6:1, to obtain the compound of formula (3), with a yield of 60%.
[0062] Step S2, synthesis of compound of formula (7): Compound of formula (6) (0.88 g, 2.72 mmol) was added to a 100 mL double-necked bottle, tetrabutylammonium bromide (0.32 g, 0.27 mmol) was dissolved in dibromobutane (20 mL), and then 50% potassium hydroxide aqueous solution (5 mL) was added dropwise. The mixture was heated to 65° C. and then stirred overnight. The reaction was quenched with water, extracted with dichloromethane, the organic layer was combined with anhydrous magnesium sulfate and dried, and then the organic solvent was removed by rotary evaporator to obtain a crude product. Silica gel column chromatography was used, and the eluent was petroleum ether / dichloromethane = 10 / 1 for further purification to obtain compound of formula (7) (0.89 g, yield 88%).
[0063] Step S3, synthesis of compound of formula (8): Compound of formula (7) (1.38 g, 3.0 mmol) and triethyl phosphite (10 mL) were added to a 100 mL double-necked bottle, and the mixture was heated to 160° C. and stirred overnight under a nitrogen atmosphere. The mixture was extracted with dichloromethane, the organic layer was combined with anhydrous magnesium sulfate and dried, and then the organic solvent was removed by a rotary evaporator to obtain a crude product compound of formula (8) (1.12 g, 2.21 mmol), with a yield of 70%.
[0064] Step S4, synthesis of the compound of formula (9): under inert gas protection, in a 100mL double-necked bottle, add the compound of formula (8) (1.06g, 2.0mmol), the compound of formula (5) (1.39g, 4.4mmol) and palladium acetate (0.1mmol), tri-tert-butylphosphine (0.1mmol), sodium tert-butoxide (4mmol) dissolved in toluene: isopropanol (1:8) mixed solution, react at 85°C for 6 to 15h. Cool to room temperature, decompress and spin-dry the isopropanol toluene mixed solution, wash and extract with saturated sodium chloride solution and dichloromethane, dry with anhydrous magnesium sulfate, filter, and distill under reduced pressure to obtain a crude product. Recrystallize from ethanol (methanol) / dichloromethane to obtain the compound of formula (9) (1.51g, 1.5mmol), with a yield of 75%.
[0065] Step S5, synthesis of PACZ-OMe: Add the compound of formula (5) (2.01 g, 2 mmol) to anhydrous 1,4-dioxane (10 mL) at room temperature in a 100 mL double-necked flask, add trimethylsilyl bromide (3.06 g, 20 mmol) dropwise, and then stir overnight. Remove 1,4-dioxane with a rotary evaporator to obtain a solid powder. The solid powder was dissolved in methanol (10 mL) at room temperature, and then deionized water was added dropwise and stirred for another 12 hours. The crude product was collected by filtration and washed with deionized water to obtain a crude product. The crude product was dissolved in THF (5 mL), reprecipitated in acetone (20 mL), and filtered to obtain the final product, PACZ-OMe (1.61 g, yield 85%).
[0066] Example 2
[0067] The synthesis of PACZ-SMe, the synthesis route is as follows:
[0068]
[0069] Step S1, synthesis of the compound of formula (5): weigh the compound of formula (1) (1.1 g, 4 mmol), the compound of formula (4) (0.53 g, 4.2 mmol), Pd2(dba)3 (0.18 g, 0.2 mmol), DPPF (0.11 g, 0.2 mmol), sodium tert-butoxide (0.38 g, 4 mmol) and toluene into a flask, react at 120° C. for 12 hours. DCM extraction, drying over anhydrous magnesium sulfate, column chromatography with PE:DCM ratio of 6:1, to obtain the compound of formula (5), with a yield of 60%.
[0070] Step S2, synthesis of compound of formula (7): Compound of formula (1) (0.88 g, 2.72 mmol) was added to a 100 mL double-necked bottle, tetrabutylammonium bromide (0.32 g, 0.27 mmol) was dissolved in dibromobutane (20 mL), and then 50% potassium hydroxide aqueous solution (5 mL) was added dropwise. The mixture was heated to 65° C. and then stirred overnight. The reaction was quenched with water, extracted with dichloromethane, the organic layer was combined with anhydrous magnesium sulfate and dried, and then the organic solvent was removed by rotary evaporator to obtain a crude product. Silica gel column chromatography was used, and the eluent was petroleum ether / dichloromethane = 10 / 1 for further purification to obtain compound of formula (7) (0.89 g, yield 88%).
[0071] Step S3, synthesis of the compound of formula (8): Add the compound of formula (2) (1.38 g, 3.0 mmol) and triethyl phosphite (10 mL) into a 100 mL double-necked bottle, then heat the mixture to 160° C. and stir overnight under a nitrogen atmosphere. Extract with dichloromethane, dry the organic layer with anhydrous magnesium sulfate, and then remove the organic solvent with a rotary evaporator to obtain a crude product of the compound of formula (8) (1.12 g, 2.21 mmol), with a yield of 70%.
[0072] Step S4, synthesis of the compound of formula (10): under inert gas protection, in a 100mL double-necked bottle, add the compound of formula (8) (1.06g, 2.0mmol), the compound of formula (5) (1.46g, 4.4mmol) and palladium acetate (0.1mmol), tri-tert-butylphosphine (0.1mmol), sodium tert-butoxide (4mmol) dissolved in toluene: isopropanol (1:8) mixed solution, react at 85°C for 6 to 15h. Cool to room temperature, decompress and spin-dry the isopropanol toluene mixed solution, wash and extract with saturated sodium chloride solution and dichloromethane, dry with anhydrous magnesium sulfate, filter, and distill under reduced pressure to obtain a crude product. Recrystallize from ethanol (methanol) / dichloromethane to obtain the compound of formula (10) (1.55g, 1.5mmol), with a yield of 75%.
[0073] Step S5, synthesis of PACZ-SMe: Add the compound of formula (10) (2.06 g, 2 mmol) to anhydrous 1,4-dioxane (10 mL) at room temperature in a 100 mL double-necked flask, add trimethylsilyl bromide (3.06 g, 20 mmol) dropwise, and then stir overnight. Remove 1,4-dioxane with a rotary evaporator to obtain a solid powder. The solid powder was dissolved in methanol (10 mL) at room temperature, and then deionized water was added dropwise and stirred for another 12 hours. The crude product was collected by filtration and washed with deionized water to obtain a crude product. The crude product was dissolved in THF (5 mL), reprecipitated in acetone (20 mL), and filtered to obtain the final product, PACZ-SMe (1.63 g, yield 85%).
[0074] Examples 3 to 4
[0075] The difference from Example 1 is that the parameters of step S1 are different:
[0076] Table 1
[0077]
[0078] Examples 5 to 6
[0079] The difference from Example 1 is that the parameters of step S2 are different:
[0080] Table 2
[0081]
[0082]
[0083] Examples 7 to 8
[0084] The difference from Example 1 is that the parameters of step S3 are different:
[0085] Table 3
[0086]
[0087] Examples 9 to 10
[0088] The difference from Example 1 is that the parameters of step S4 are different:
[0089] Table 4
[0090]
[0091]
[0092] Examples 11 to 12
[0093] The difference from Example 1 is that the parameters of step S5 are different:
[0094] Table 5
[0095]
[0096] To further evaluate the effects of PACZ-SMe and PACZ-OMe as HTMs on the photovoltaic performance of inverted quasi-2D RP PSCs, a device with the structure of ITO glass / polymer HTM / quasi-2D RP perovskite / PC61BM / Cr / Au was fabricated. The perovskite absorber layer is composed of (3FBA)2MA3Pb4I 13 Composition (3FBA = 3-fluorobenzylammonium, MA = methylammonium), PC61BM is used as an electron transport material (ETM), Cr and Au are used as a charge blocking layer and a cathode, respectively. The phosphate carbazole material prepared in the above embodiment is prepared into an inverse quasi-two-dimensional perovskite solar cell according to the following method:
[0097] (1) Cleaning: The ITO glass sheet was ultrasonically cleaned with deionized water, acetone, and ethanol for 20 minutes in sequence. The residual solvent on the surface of the ITO was then blown dry with a N2 air gun. The ITO glass sheet was then treated with oxygen plasma for 15 minutes. The ITO glass sheet was then transferred to a nitrogen glove box.
[0098] (2) Preparation of hole transport layer: 15 mg of phosphate carbazole hole transport material was weighed and completely dissolved in 1 mL of chlorobenzene solution. An appropriate amount of the solution was evenly dropped onto the ITO glass substrate, and the solution was spin-coated at 5000 rpm for 30 seconds, and then annealed at 110° C. for 10 minutes.
[0099] (3) Preparation of perovskite layer: The ITO / hole transport layer substrate obtained above was cooled to room temperature, preheated at 140°C for 3-5 minutes, 50 μL of perovskite solution was spread over the ITO / hole transport layer substrate, spin coated at 5000 rpm for 30 seconds, and then annealed at 100°C for 10 minutes to prepare a perovskite layer. The perovskite solution is prepared by mixing 3-bromo-benzylammonium iodide or 3-chlorobenzylammonium iodide, methylammonium chloride, and lead iodide in DMF and DMSO in a certain molar ratio;
[0100] (4) Preparation of electron transport layer: The ITO / hole transport layer / perovskite substrate obtained above was cooled to room temperature, PC61BM was prepared into a 15 mg / mL solution, and then 40 μL of the PC61BM solution was spread over the ITO / hole transport layer / perovskite substrate, and spin-coated at 1000 rpm for 30 to 50 seconds;
[0101] (5) Preparation of electrodes: The above substrate is placed in a vacuum evaporation chamber, and Cr (6 nm) and Au (80 nm) are evaporated on the PC61BM layer respectively, thereby obtaining the desired inverse quasi-two-dimensional perovskite solar cell.
[0102] The NMR spectrum of the phosphate carbazole material of Example 1 is shown in Figure 1 The nuclear magnetic spectrum of the phosphate carbazole material of Example 2 is shown in Figure 2 ; The schematic diagram of the structure of the perovskite solar cell of Example 1 is shown in Figure 3 .
[0103] The film-forming properties, structural stability and photoelectric properties of the phosphate carbazole materials prepared in the above examples were measured.
[0104] Test method:
[0105] Film-forming properties: PACZ-SMe and PACZ-OMe as HTM substrates are conducive to the diffusion and growth of quasi-two-dimensional perovskites, thereby obtaining dense, uniform, and smooth perovskite films. The crystal growth of quasi-two-dimensional perovskite films on different polymer HTMs was studied using AFM. Quasi-two-dimensional perovskite films based on PACZ-Sme or PACZ-OMe showed lower RMS roughness, respectively.
[0106] Structural stability: The stability of quasi-2D perovskite solar cells with different HTMs was studied. After 1200 hours of storage in an inert environment, the unencapsulated quasi-2D perovskite solar cells with PACZ-Sme or PACZ-OMe were tested to see what percentage of their initial efficiency they retained.
[0107] Photoelectric performance: 0.02V s under AM 1.5G lighting conditions -1 The JV curve of the best device is measured by forward and reverse scanning, and the photovoltaic index V is obtained. oc 、Short circuit current density (J sc ), fill factor (FF) and photoelectric conversion efficiency (PCE).
[0108] Among them, the full parameters of the photoelectric performance of Examples 1 and 2 are shown in Table 6, and the performance test results of each example are shown in Table 7.
[0109] Table 6
[0110]
[0111] Table 7
[0112]
[0113]
[0114] As can be seen from the above, each embodiment of the present invention uses phosphocarbazole as the main structure, which has the ability to be evenly coated on rough surfaces and has high hole extraction selectivity, as well as low interface electron trap density, and can therefore be used as an excellent hole-selective contact layer. At the same time, pyridine groups are introduced therein to adjust the photophysical, electrochemical and photovoltaic properties, showing improved surface wettability of the perovskite precursor solution, thereby inducing the growth of high-quality perovskite films; the N atoms and amino groups with lone pairs of electrons in pyridine can both react with uncoordinated Pb in the perovskite. 2+ The formation of coordinated bond ions effectively reduces the defect density in the perovskite film; the introduction of pyridine groups can also enhance hole mobility and improve energy levels, thereby improving interface charge extraction and reducing interface V oc loss; pyridine generates excellent inherent thermal / photostability and stronger interaction at the interface to release interface stress, so that the thermal performance and operational stability of perovskite solar cells are improved. The phosphate carbazole hole transport material of the present invention has good solubility, film-forming property, high hole mobility and energy level matching with perovskite. It can be used as an undoped hole transport material in perovskite solar cells to obtain good photoelectric conversion efficiency, and realize low-cost, high-performance, stable, large-area perovskite solar cell applications. In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the comprehensive effect is better.
[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A carbazole phosphate material, characterized in that: It has the structure shown in general formula (I): Wherein, A is O or S.
2. The method for preparing the phosphate carbazole material according to claim 1, characterized in that: The preparation method is carried out under the protection of inert gas and comprises the following steps: Step S1: A first palladium catalyst and a first base are mixed and dissolved in a first solvent, and a first coupling reaction is performed to obtain Where A is O or S; Step S2: Dibromobutane, a substitution catalyst, and a second base are mixed to carry out a first nucleophilic substitution reaction to obtain Step S3: Triethyl phosphite was mixed and a second nucleophilic substitution reaction was performed to obtain Step S4: The second palladium catalyst and the third base are mixed and dissolved in the second solvent, and a second coupling reaction is performed to obtain Step S5: The trimethylsilyl bromide and 1,4-dioxane are mixed and subjected to a hydrolysis pre-reaction to obtain a solid product; the solid product is dissolved in methanol and water is added dropwise to perform a hydrolysis reaction to obtain 3. The preparation method according to claim 2, characterized in that: In the step S1, The first palladium catalyst comprises tris(dibenzylideneacetone)dipalladium and 1,1'-bis(diphenylphosphine)ferrocene ligand, and the molar ratio of the two is 1:(0.8-1.2); and / or and The molar ratio is 1:(1.0-1.1); and / or The molar ratio of the first palladium catalyst to the first palladium catalyst is 1:(0.08-0.12); and / or The reaction temperature of the first coupling reaction is 100-140° C., and the reaction time is 10-14 hours.
4. The preparation method according to claim 2 or 3, characterized in that: In the step S2, The substitution catalyst comprises tetrabutylammonium bromide; and / or The ratio of the amount of substance to the volume of dibromobutane is (2.5-3.0 mmol): 20 mL; and / or The molar ratio of the substituted catalyst is 1:(0.08-0.12); and / or The reaction temperature of the first nucleophilic substitution reaction is 60-70° C., and the reaction time is 10-14 hours.
5. The preparation method according to any one of claims 2 to 4, characterized in that: In the step S3, The ratio of the amount of substance to the volume of triethyl phosphite is (2.8-3.2 mmol): 10 mL; and / or The reaction temperature of the second nucleophilic substitution reaction is 130-160° C., and the reaction time is 10-14 h.
6. The preparation method according to any one of claims 2 to 5, characterized in that In the step S4, The second palladium catalyst comprises palladium acetate and tri-tert-butylphosphine ligand, and the molar ratio of the two is 1:(0.8-1.2); and / or and The molar ratio is 1:(2.0-2.4); and / or The molar ratio of the second palladium catalyst is 1:(0.08-0.12); and / or The reaction temperature of the second coupling reaction is 65-85° C., and the reaction time is 6-15 h.
7. The preparation method according to any one of claims 2 to 6, characterized in that In the step S5, The molar ratio of trimethylsilyl bromide to trimethylsilyl bromide is 1:(9.5-10.5); and / or The ratio of the amount of substance to the volume of 1,4-dioxane is (1.8-2.2 mmol): 10 mL; and / or The temperature of the hydrolysis pre-reaction is 20-30°C and the time is 10-14h; the temperature of the hydrolysis reaction is 20-30°C and the time is 10-14h.
8. The preparation method according to any one of claims 2 to 7, characterized in that: The inert gas comprises nitrogen and / or argon; and / or The first base, the second base and the third base independently include one or more of sodium tert-butoxide, potassium hydroxide, potassium carbonate and sodium carbonate; and / or The first solvent comprises toluene and / or tetrahydrofuran; and / or The second solvent includes toluene and isopropanol, and the weight ratio between the two is 1:(6-10).
9. A hole transport layer, characterized in that: The invention comprises the phosphate carbazole material according to claim 1, or comprises the phosphate carbazole material obtained by the preparation method according to any one of claims 2 to 8.
10. A perovskite solar cell, characterized in that: The method comprises the hole transport layer as claimed in claim 9.
Citation Information
Patent Citations
Hole-transporting self-organised monolayer for perovskite solar cells
CN112469727A
Synthesis of carbazole-based small organic molecule hole transport material and application of carbazole-based small organic molecule hole transport material in perovskite solar cell
CN113185449A
Indolocarbazole-based self-assembled monomolecular layer hole transport material and synthesis method and application thereof
CN114874263A
Self-assembly hole transport material based on 7H-dibenzocarbazole and synthesis method
CN115215901A
Hole transport material, preparation method thereof and perovskite solar cell
CN119504859A